2018
DOI: 10.1007/s00520-018-4042-3
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer survivor’s perspectives on the role different providers play in follow-up care

Abstract: Importance: Significant variation in the number and types of oncologists that provide breast cancer follow-up exists. However, there is limited understanding regarding breast cancer survivors’ preferences for who provides their follow-up. Our objective was to explore breast cancer survivors’ perspectives on the goals of breast cancer follow-up, the preferred role for primary care providers, and the perceived roles of different types of oncologists during follow-up. Methods: A convenience sample of stage 0-II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The majority of patients prefer their PCPs to manage chronic comorbid conditions, but in a population‐based study of >2000 women with stages 0 to II BC, approximately 20% of patients preferred their oncologists to manage general preventive and comorbidity care compared with their PCPs . This may be related to patients' preference for oncology‐focused care within the first years after diagnosis, when patients are most concerned about disease recurrence . Other barriers to PCP participation in BC survivorship include lack of coordinated care, fragmented provider‐to‐provider communication, and changes to the care team as a result of postdiagnosis insurance plan changes or changes regarding the acceptance of insurance plans by physicians .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of patients prefer their PCPs to manage chronic comorbid conditions, but in a population‐based study of >2000 women with stages 0 to II BC, approximately 20% of patients preferred their oncologists to manage general preventive and comorbidity care compared with their PCPs . This may be related to patients' preference for oncology‐focused care within the first years after diagnosis, when patients are most concerned about disease recurrence . Other barriers to PCP participation in BC survivorship include lack of coordinated care, fragmented provider‐to‐provider communication, and changes to the care team as a result of postdiagnosis insurance plan changes or changes regarding the acceptance of insurance plans by physicians .…”
Section: Discussionmentioning
confidence: 99%
“…20 This may be related to patients' preference for oncologyfocused care within the first years after diagnosis, when patients are most concerned about disease recurrence. [21][22][23] Other barriers to PCP participation in BC survivorship include lack of coordinated care, fragmented provider-to-provider communication, and changes to the care team as a result of postdiagnosis insurance plan changes or changes regarding the acceptance of insurance plans by physicians. [21][22][23][24][25] To our knowledge to date, interventions to enhance communication between oncology specialists and PCPs have not proven to be successful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCPs in this study indicated perspectives on the frequency of aftercare widely ranging from leaving the responsibility for organisation of aftercare with the patients as much as possible to providing a structured program with planned care moments, to make sure that all patients receive sufficient aftercare. Additionally, HCPs involved in aftercare varied considerably in disciplines and coordination of care, possibly due to a lack of standard protocols as seen in other studies (Neuman et al, 2017;Tucholka et al, 2018). One way to streamline care and to reduce inefficiency is to appoint a case manager that has an overview of the care process and acts as a contact person for patients.…”
Section: Discussionmentioning
confidence: 99%
“…The Dutch Breast Cancer Association (BVN) provided input for the study design and patient representatives were present at two interviews. A considerable amount of information about the needs and preferences of patients in breast cancer follow‐up is already present in literature (Berendsen et al, 2016 ; Brandenbarg et al, 2017 ; Feiten et al, 2016 ; Kwast et al, 2013 ; Lubberding et al, 2015 ; Onuma et al, 2019 ; Tucholka et al, 2018 ; van Hezewijk et al, 2011 ).…”
Section: Strengths and Limitationsmentioning
confidence: 99%